The Benefits of Sharia Insurance for MSMEs at PT Zurich Asuransi Indonesia Tbk - Arista Fitri Diana; Zakaria Bani IKhtiyar; Putri Ardelia, Nova (Journal of Applied Statistics and Data Mining, 2025)
Background: Islamic insurance in Indonesia has grown significantly into a modern financial institution capable of competing with conventional insurance. In this context, the micro, small, and medium enterprises (MSMEs) sector is among the major beneficiaries, as Islamic insurance offers protection aligned with the values and needs of the Muslim community. The Indonesian government continues to promote the development of Islamic microinsurance as part of its strategy to strengthen the halal industry and support the economic resilience of MSMEs. Objective: This study aims to examine in depth the benefits of Islamic insurance for MSMEs in Indonesia, with a particular focus on PT Zurich Asuransi Indonesia Tbk as a provider of Islamic insurance products designed to support the MSME sector.t did you want to find out? Methods: This research uses a literature review methodology by analyzing various academic sources, government policies, and industry reports related to the development and implementation of Islamic insurance for MSMEs in Indonesia. Results: The findings show that Islamic insurance provides various benefits to MSMEs, including protection against operational risks, natural disasters, and economic uncertainty. Innovative and effectively managed Islamic microinsurance products enable MSMEs to access affordable protection. PT Zurich Asuransi Indonesia Tbk plays an active role in offering insurance products that are compliant with sharia principles and tailored to the specific needs of MSMEs. Conclusion: This study concludes that Islamic insurance is an important instrument in supporting the sustainability and growth of MSMEs in Indonesia. The protection it offers serves not only as a financial safety net but also as a driver of a sharia-based economy. Future research should explore the empirical impact of Islamic insurance products on the long-term resilience and development of MSMEs.